Commitment and conflict in multilateral bargaining - Miettinen, Topi; Vanberg, Christoph (Discussion paper series, 2020)
We extend the Baron and Ferejohn (1989) model of multilateral bargaining by allowing the players to attempt commiting to a bargaining position prior to negotiating. If successful, commitment binds a player to reject any proposal which allocates to her a share below a self-imposed threshold. Any such attempted commitment fails and decays with an exogenously given probability. We characterize and compare symmetric stationary subgame perfect equilibria under unanimity rule and majority rules. Under unanimity rule, there are potentially many equilibria which can be ordered from the least to most inefficient, according to how how many commitment attempts must fail in order for an agreement to arise. The most inefficient equilibrium exists independently of the number of players, and the delay in this equilibrium is increasing in the number of players. In addition, more efficient commitment profiles cannot be sustained in equilibrium if the number of players is sufficiently large. The expected inefficiency due to delay at the least and at the most efficient equilibrium increases as the number of players increases. Under any (super)majority rule, however, there is no equilibrium with delay or inefficiency. The reason is that competition to be included in the winning coalition discourages attempts to commit to an aggressive bargaining position. We also show that inefficiencies related to unanimity decision making may be aggravated by longer lags between consecutive bargaining rounds. The predicted patterns are by and large consistent with observed inefficiencies in many international arenas including the European Union, WTO, and UNFCCC. The results suggest that the unanimity rule is particularly damaging if the number of legislators is large and the time lags between consecutive sessions are long.
Keywords: Graue Literatur